Post-COVID-19 human memory impairment: A PRISMA-based systematic review of evidence from brain imaging studies - Shan, Dan; Li, Shaoyang; Xu, Ruichen; Nie, Glen; Xie, Yangyiran; Han, Junchu; Gao, Xiaoyi; Zheng, Yuandian; Xu, Zhen; Dai, Zhihao (Frontiers in Aging Neuroscience, 2022)
Many people with coronavirus disease 2019 (COVID-19) report varying degrees of memory impairment. Neuroimaging techniques such as MRI and PET have been utilized to shed light on how COVID-19 affects brain function in humans, including memory dysfunction. In this PRISMA-based systematic review, we compared and summarized the current literature looking at the relationship between COVID-19-induced neuropathological changes by neuroimaging scans and memory symptoms experienced by patients who recovered from COVID-19. Overall, this review suggests a correlational trend between structural abnormalities (e.g., cortical atrophy and white matter hyperintensities) or functional abnormalities (e.g., hypometabolism) in a wide range of brain regions (particularly in the frontal, parietal and temporal regions) and memory impairments in COVID-19 survivors, although a causal relationship between them remains elusive in the absence of sufficient caution. Further longitudinal investigations, particularly controlled studies combined with correlational analyses, are needed to provide additional evidence.